E-Business through Social Media - Soegoto, Eddy Soeryanto; Aqila, B K (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to find out how marketing communication strategies are used in online business. The method of this research used a descriptive method. The results of this research show that doing business is not difficult; the seller can open an online business. Through marketing communication strategies that are attracting and right to the segmentation. As a result of the business that the seller organize can develop well.